Development of Audio-Visual Learning Media on Molecular Gastronomy Material - Rinawati, Wika; Salsabila, Adelia (Green Publisher Indonesia, 2023)
This research aims to: 1) Develop audio-visual learning media on molecular gastronomy topics, 2) Determine the feasibility of audio-visual learning media on molecular gastronomy topics. This study is a research and development (R&D) study through the 4D development model consisting of define, design, develop, and disseminate. The results of the development of audio-visual learning media on molecular gastronomy topics can be described as follows: a) The media has a duration of 12 minutes and 15 seconds, b) The learning media format is in the form of an mp4 video sized at 420.1 MB, c) The sections of the media are divided into the opening stage, aperception material, core material containing explanations about the definition of molecular gastronomy, techniques in molecular gastronomy, practice of making imitation caviar using gelification techniques, evaluation quizzes, and conclusion, d) The media dissemination is done by uploading it through the YouTube platform on the BOGA UNY channel with the URL https://youtu.be/61-ZqZIXkSA. The results of the feasibility assessment of audio-visual learning media on molecular gastronomy topics by subject matter experts received an average score of 100%, which falls into the highly feasible category. Evaluation by media experts resulted in an average score of 95.19%, also classified as highly feasible. The assessment by students yielded an average score of 84.29% on a small scale and 89.71% on a large scale, both falling into the highly feasible category. Based on the feasibility test results, the audio-visual learning media on molecular gastronomy topics is declared highly suitable for use as a learning medium.